Management challenges for transitioning the adolescent with vertically transmitted HIV/Aids between reference services - Fabiana Cristine dos Santos; Cintia Koerich; Alacoque Lorenzini Erdmann; Betina Hörner Schlindwein Meirelles (Universidade Federal de Goias, 2014)
The present study aims at defining the structure and functioning of HIV/Aids reference services in a state in southern Brazil which care for adolescents with vertically transmitted HIV/Aids. It examines the transition process between child and adult reference services and the contribution of nursing professionals towards this process, in the capacity of health services managers. It is a qualitative and descriptive study, whose data was gathered through participative observation and individual interviews with ten participants. The data was analyzed thematically and discussed in three categories: Presenting the structure of child and adult HIV/Aids reference services; Welcoming and accompanying adolescents with vertically transmitted HIV/Aids to reference services; The nursing professional as a health care manager in HIV/Aids reference services, which pointed to the necessity for investments in infrastructure, support and planning of management actions, health management professional training and education, in order to assure the quality of care transition. doi: 10.5216/ree.v16i2.21666.